HISTOCHEMICAL CHANGES IN LEYDIG CELLS AND SEMINIFEROUS TUBULES OF MICROCHIROPTERAN BAT HIPPOSIDEROS SPEORIS (SCHNEIDER) DURING TESTICULAR CYCLE - M. S. SASTRY; SUSHMITA CHOUDHURY (The Bioscan, 2011)
Hipposideros speoris is an insectivorous bat and breeds once in a year. For the demonstration of oxidative enzymes namely succinic dehydrogenase (SDH) and glucose-6-phosphate dehydrogenase (G-6-PDH) throughout the annual reproductive cycle the testis were histochemically studied. Correlative to the reproductive status specific changes in the enzymatic reaction were observed. Thus during quiescense (April-August) a moderate activity in the Leydig cells whereas very low reactivity in the seminiferous tubules for both the enzymes was observable. With the approach of maturity (recrudescence: September-October) an enhanced activity reflecting high intensity in the Leydig cells whereas in the seminiferous tubules similar intensity expressed by granular formazan deposition. Massive deposition of formazan granules characterized this period (breeding period: November-December), however, there appeared differential distribution of the granules being even all over the seminiferous tubule while concentrated at one spot in Leydig cells. The characteristic features of the regression period (January-March) were prominent decrease in the intensity of enzymes which was almost negligible in the seminiferous tubules. From the foregoing, it is concluded that the annual reproductive cycle and enzymic activity go vis-à-vis.